Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1103/physreve.99.042138
|View full text |Cite
|
Sign up to set email alerts
|

Infinite ergodic theory for heterogeneous diffusion processes

Abstract: We show the relation between processes which are modeled by a Langevin equation with multiplicative noise and infinite ergodic theory. We concentrate on a spatially dependent diffusion coefficient that behaves as D(x) ∼ |x −x| 2−2/α in the vicinity of a pointx, where α can be either positive or negative. We find that a nonnormalized state, also called an infinite density, describes statistical properties of the system. For processes under investigation, the time averages of a wide class of observables, are obt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 48 publications
(98 reference statements)
0
68
0
Order By: Relevance
“…This happens, for example, if x n is symmetric with respect to the starting point. Indeed, we could obtain the same from renewal theory, see [15][16][17][18] and references therein. It is worth observing that the parameter characterizing the distribution of the occupation time of the origin must be the same parameter of the Lamperti distribution, which in our setting describes the occupation time of the positive(negative) axis for a symmetric process.…”
Section: Number Of Visits At the Originmentioning
confidence: 99%
“…This happens, for example, if x n is symmetric with respect to the starting point. Indeed, we could obtain the same from renewal theory, see [15][16][17][18] and references therein. It is worth observing that the parameter characterizing the distribution of the occupation time of the origin must be the same parameter of the Lamperti distribution, which in our setting describes the occupation time of the positive(negative) axis for a symmetric process.…”
Section: Number Of Visits At the Originmentioning
confidence: 99%
“…Smyshlyaev and Chen applied a position-dependent diffusion coefficient to the boundary feedback control of a diffusive system and proved the Mittag-Leffler stability of the system [45,46]. Several other works have since focussed on position-dependent diffusive systems [47][48][49][50], to name but a few.Differing from a constant diffusion coefficient, the presence of a position-dependent diffusivity involves the problem of how to interpret multiplicative noise in a stochastic equation, particularly, a noise-induced drift, which varies by choosing different integral forms, such as Itô, Stratonovich and isothermal integrals [44,51]. It is found that the probability distribution generated within the isothermal integral formulation effects the required Boltzmann distribution, which is correct in thermal equilibrium state [48][49][50], while the Itô and Stratonovich integrals lead to 'athermal' forms.…”
mentioning
confidence: 99%
“…Several other works have since focussed on position-dependent diffusive systems [47][48][49][50], to name but a few.Differing from a constant diffusion coefficient, the presence of a position-dependent diffusivity involves the problem of how to interpret multiplicative noise in a stochastic equation, particularly, a noise-induced drift, which varies by choosing different integral forms, such as Itô, Stratonovich and isothermal integrals [44,51]. It is found that the probability distribution generated within the isothermal integral formulation effects the required Boltzmann distribution, which is correct in thermal equilibrium state [48][49][50], while the Itô and Stratonovich integrals lead to 'athermal' forms. Generally, the Itô interpretation is employed in economics and biology due to their features of being 'only related to the latest past'; the Stratonovich integral finds applications in physical systems, such as electrical circuits driven by multiplicative noises (see [51], and references therein).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that the more general approach of Refs. [21][22][23][24] employing a position-dependent diffusivity that does not depend on the position through the concentration.…”
Section: Discussionmentioning
confidence: 99%